Peculiarities of construction of local self-government models in the modern slavic states - A. Djordjević; A. Seregin; M. Cherkasova; I. Milkina (Управление)
The peculiarities of construction of local self-government models in the modern Slavic States, which in the 90-s of XX century abandoned the socialist path of development, – have been examined. The aim of the study is to identify specific features and common approaches to the construction of local self-government system, based on the analysis of the practice of local self-government institutions of the Slavic States and the provisions of the Constitutions of the Republic of Serbia, the Republic of Poland, the Czech Republic, the Slovak Republic, Ukraine, the Republic of Croatia, the Russian Federation, etc.The organizational forms of local self-government and the particularities of the implementation of local issues, taking into account national traditions, – have been analyzed. In this connection, the majority of modern Slavic States recognizes and guarantees local self-government as the most important constitutional value and institution of the people’s right. It has been determined, that the list of issues of local importance mainly affects the areas of urban planning, municipal activities, culture, sports, social protection of the population and children, preschool education, healthcare, approval of municipal programs of economic development, local budgets, taxes and fees, the appointment of local referendums, etc. However, there there is a number of countries, in which local government issues are not specified in the Constitution. Among the criteria for the difference between the models of local self-government are the following: the list of issues of local importance and competence of local self-government bodies; relations with public authorities and the degree of freedom of local self-government from the state; territorial organization of local self-government, etc.It has been concluded, that the most common form of interaction between public authorities and local self-government for the Slavic states at the beginning of the XXI century, was the Zemstvo-state model, that takes into account the mutual interests of a sovereign power and the population, living within certain territorial communities.